Gebe Language usage in Central Halmahera - Nurain Jalaludin; Ismail Maulud; Z Zainurrahman (Program Studi Pendidikan Bahasa Inggris, ISDIK Kie Raha Maluku Utara, 2023)
This study aims to study the pattern of use of the Gebe language on Gebe Island, Central Halmahera, North Maluku. Gebe Island is a multi-ethnic island located in Central Halmahera, which was originally an island with a single ethnicity, namely the Gebe ethnicity itself. Over time, social, economic and cultural dynamics have brought about rapid changes in the linguistic life of the Gebe native people. The establishment of a nickel mine on the island in 1978 has invited immigrants from various linguistic backgrounds to come to the island. Designed as a descriptive qualitative study, we identified at least seven domains of language use where the local Gebe language experienced a rapid decline. The causative factors include mobility, inter-ethnic marriage, and minimal effort to transfer this language from the older generation to the younger generation as an effort to preserve the language. Our study has come to a conclusion that the Gebe local language currently requires attention from both its speakers and the government.